Review on building energy effeciency through optimized building envelopes - Bazaraah, Maryam Omar; Khodeir, Laila; Gadelhak, Mahmoud (Journal of engineering sciences and information technology, 2024)
Energy-efficient building envelopes consider material thermophysical properties and wall section configuration to optimize energy consumption for cooling and heating in response to climate. A review of 80 papers revealed that published information on this subject is diverse, contains inconsistencies in findings, and shows contradictory results. Therefore, hypothesizing a suitable building envelope for efficient year-round performance per climate is difficult through published literature alone. The aim of this paper is to identify trends and gaps in studies regarding efficient year-round building envelopes. Relevant literature published from 1997 to 2023 was reviewed. A data extraction process was used to organize performance parameters of thermal insulation and thermal mass. The relationships between climate, wall configuration, and thermophysical properties in published experimental studies were then analyzed. Results of static thermal insulation investigations revealed a trend where the most common placement is interior or embedded, however inconsistencies in results were found depending on climate. Dynamic insulation is predicted to show promising results, although it is a novel solution under research. Moreover, multilayer walls of thermal insulation and thermal mass show better mitigation for thermal discomfort in climates with high diurnal fluctuation compared to other climates. Furthermore, latent heat storage using Phase Change Materials (PCMs) was found to be more advantageous than sensible heat storage. This study highlights future potential research on building envelopes in different climates and microclimates and their respective thermophysical properties requirements.
Keywords: Static Insulation; Dynamic Insulation; Sensible Heat Storage; Latent Heat Storage; Year-round Energy Efficiency